Analisis Implementasi Governasi Digital Dalam Penggunaan Aplikasi IKD (Identitas Kependudukan Digital) di Disdukcapil Kota Padang - Asmaniah, Asmaniah; Aulia Pratama, Nanda; Cahayani Karmila, Vira; Oktaviani, Wulan; Fitri Helmi, Rahmadhona (Orasi: Jurnal Ilmu Politik dan Sosial, 2024)
This study aims to analyze the implementation of digital governance in the use of the Digital Population Identity (IKD) application at the Population and Civil Registration Office (Disdukcapil) of Padang City. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that the implementation of the IKD application since early 2023 has improved the efficiency and effectiveness of population services. IKD facilitates community access to administrative documents through digitization, reducing the need for manual interaction with the Disdukcapil office. However, the application faces internal constraints such as network problems and external constraints such as limited access to technology and low public understanding. The level of community acceptance of IKD is influenced by age, education, and availability of digital devices. To overcome these challenges, Disdukcapil Padang City coordinates with the central government, conducts field socialization, and provides manual services as an alternative. The implementation of the IKD application supports digital governance principles, such as transparency, accountability and efficiency, in line with the vision of excellent service. This study concludes that despite challenges in its implementation, IKD is a significant innovation in improving the quality of digital-based public services in Padang City.